(untitled) (REMUNOM, 2025)
This article analyzes the impacts of cybercrime on civil liability, highlighting the growing incidence of cybercrimes and their impact on interpersonal relationships in digital environments. The central issue of this study is understanding the extent to which Brazilian law offers effective punishment and prevention tools in the face of the challenges of anonymity and transnationality imposed by the digital age. The research, of a bibliographical and documentary nature, was based on the 2002 Civil Code and specific legislation—such as the Internet Civil Framework and the General Data Protection Law—as well as an analysis of doctrines and case law. The methodology used demonstrated regulatory gaps, the difficulty of using traditional means to enforce the rules, and the need for harmonization between the Civil Code and Special Legislation. The study demonstrates the importance and urgency of discussing the protection of rights in virtual environments, given the growth of cybercrimes, which impact both individuals and the community as a whole. Through critical and comparative analysis of the traditional Brazilian legal system and special legislation, results were presented that demonstrate progress in addressing the problem. However, they also highlight the need for regulatory and jurisprudential updates to create a safe and suitable virtual environment for everyone.